Trichoptera of he Santuario de Iguaque (Boyacá, Colombia) in relation to water quality - MEDELLÍN-C., FRANCISCO; RAMÍREZ-O., MÓNICA; RINCÓN, MARÍA EUGENIA (Revista Colombiana de Entomología, 2004)
Results are presented that were obtained during research conducted in sorne of the main bodies of water in the lquaque Fauna and Flora Sanctuaries. Boyacá: Carrizal, Mamarramos, Colorada mountain streams and the Cane River. The physical-chemical characteristics and composition of the thrichopteran fauna were studied using the choriotopes sampling technique during the months from September 2001 to April 2002. Three samples were taken covering periods of high and low precipitation in order to analyze sorne physical and chemical elements and composition of thrichopteran fauna. lt was found that rain regime had an influence on the biological and physical chemical conditions causing a reduction in the abundance of the thrichopteran community during the months of high precipitation (April-May) and an increase in abundance when rains decreased. In all of the systems, 3.281 individuals distributed in 10 families and 19 genera were recorded. The genera Contulma and Ochrotrichia were predominant. with 45,68 and 16,36%, respectively. Culoptila and Metrichia were reported as new records for the zone. On the other hand. sorne species of the genera Contulma, Ochrotrichia, Helicopsyche and Mortoniella are considered as possible bioindicators for the zone.